IMMU-19. IDENTIFICATION OF TARGET ANTIGENS FOR CHIMERIC ANTIGEN RECEPTOR T- CELL THERAPY AGAINST GLIOBLASTOMA USING A MONOCLONAL ANTIBODY LIBRARY RAISED AGAINST PATIENT-DERIVED TUMOR SPHERES. (14th November 2022) - Kijima, Noriyuki; Nakagawa, Tomoyoshi; Hasegawa, Kana; Ikeda, Shunya; Yaga, Moto; Wibowo, Tansri; Kuroda, Hideki; Hirayama, Ryuichi; Okita, Yoshiko; Tachi, Tetsuro; Kagawa, Naoki; Kanemura, Yonehiro; et al.
Abstract: New therapies for GBM are urgently needed due to its poor prognosis and chimeric antigen receptor T (CAR-T) cell therapy is thought to be a promising strategy. To develop CAR-T cell therapy, cell surface targets that is highly specific for GBM cells are needed.Although extensive transcriptome analyses of GBM cells were performed, few transcripts highly specific for GBM cells have been identified. However, GBM cell-specific antigen epitopes formed by post-translational modifications of proteins may have been missed, and could still be discovered by thoroughly searching for cancer-specific monoclonal antibodies and characterizing the antigens they recognize. In this study, we applied this strategy to search for GBM-specific cell surface targets using patient derived tumor spheres. We identified two monoclonal antibodies E61 and A13 as those reacting with GBM cells but not with normal brain parenchymal cells. CAR-T cells derived from both monoclonal antibodies produced IL-2 and IFNɤ and exerted cytotoxicity to GBM cells by chromium 51 release assay. In addition, we identified B7-H3, which is frequently used for a CAR-T cell target against GBM, as the antigen recognized by B7-H3 by the expression cloning method. These results indicate that the strategy shown in this study is useful for identifying antigens that are expressed on patient-derived GBM cells and potentially useful as targets for CAR T cells.